Depression in COVID-19-positive Vaccinated Patients during Isolation and its Relation to Chronic Medical Diseases in Abu Dhabi, United Arab Emirates - Shaheen, Somaya; Adel, Shaden; Mahfouz, Noha A. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Psychological disorders are common in patients who experienced coronavirus disease 2019 (COVID-19). Thus, there is a need to assess the prevalence of these disorders following vaccination, particularly in non-hospitalized cases as most COVID-19 patients do not require hospitalization. The presence of specific chronic medical disease has been displayed to increase the severity of infection and may also cause negative psychological outcomes in these patients. AIM: This study aimed to measure the prevalence of depression in COVID-19-positive non- hospitalized vaccinated patients during isolation and to detect the difference in depression between patients with and without medical diseases within the study. METHODS: This was a cross-sectional study of a sample of patients from Abu Dhabi. A total of 194 participants were enrolled. All of them were COVID-19 vaccinated and tested positive for COVID-19. Participants were assessed using the Patient Health Questionnaire (PHQ9). RESULTS: Depression was present in 10.8% of COVID-19 positive vaccinated patients while 89.2% had no depression according to their PHQ9 scores. A total of 18.5% of patients with chronic medical diseases had depression while 9.6% of patients without chronic medical diseases showed depression with no statistical significant difference in prevalence of depression between these two groups. CONCLUSION: The prevalence of depression was relatively low in this study compared to previous studies. No significant difference was found in the likelihood of developing depression between patients with and without chronic medical diseases. Further studies should be conducted to evaluate the effect of vaccines on mental health.